A Review of Notarial Studies in the Faculty of Law: Preparing Students for the Legal Profession - Khaerunnisa, Andi Diza; Alam, Fitriani Syamsu; Apriliya, Apriliya (Journal Social Civilecial, 2025)
This literature review explores the role of notarial studies in legal education, focusing on how these studies prepare students for the legal profession. Notarial education is a key component of legal curricula, providing essential knowledge and practical skills required for handling legal documents and ensuring their authenticity. Through a comprehensive review of scholarly articles, books, and reports, this study examines the integration of notarial studies into law programs, the challenges and gaps in current educational practices, and the impact of notarial training on career readiness. The review highlights the importance of practical training, ethical instruction, and exposure to modern legal technologies in shaping competent legal professionals. Despite its significance, notarial education faces challenges such as outdated curricula, limited practical exposure, and a need for adaptation to emerging trends like digital notarization. This paper discusses the role of notarial education in enhancing students' professional competencies, focusing on their ability to navigate legal practices, uphold ethical standards, and effectively engage with clients and legal professionals. The review concludes by emphasizing the importance of reforming notarial education to address these gaps, ensuring that students are better equipped for the evolving demands of the legal field.